The foreign policies of Arab states : the challenge of globalization - Korany, Bahgat; Hilāl, ʻAlī al-Dīn; Kheir, Karen Abul; Korany, Bahgat (American University in Cairo Press, 2010)
The first edition of this book was praised as "a milestone for present and future research on Arab and Third World foreign policies" (American Political Science Review), and "an indispensable aid for those studying or teaching the foreign policies of the contemporary Middle East" (International Journal of Middle East Studies). It has become a standard textbook in Middle East studies curricula all over the world. This third edition, now in paperback, with new material reflecting the earth-shaking events at the end of the Cold War and the continuation of violence and terrorism, examines foreign.